Investigation of aspergillosis outbreak in young ducklings: Unraveling the role of hatcheries in Aspergillus fumigatus transmission (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Aspergillosis is a disease that affects several species of birds and causes substantial losses in the poultry business. The purpose of the investigation was to identify the pathogen responsible for a respiratory outbreak among juvenile ducklings. Materials and Methods: An epidemic of Aspergillosis infected a total of 800 Muscovy ducks that were being reared in El-Beheira Governorate. Tissue samples were obtained to isolate suspected fungi from diseased birds and the hatchery environment. In addition, identification and molecular characterization were performed on the obtained fungal isolates. Results: Affected birds displayed acute respiratory manifestations such as difficulty breathing, gasping for air, nasal discharge, and a mortality rate of up to 28.1%. Postmortem examination revealed bronchitis, tracheitis, congested lungs, air sacculitis, severe multifocal granulomatous pneumonia, a congested, enlarged liver, and a congested kidney with nephritis. Mycological examination revealed seven Aspergillus (A.) spp. isolates from ducklings and six from hatcheries. Isolate colonial morphology and microscopical examination were as follows: A. fumigatus, A. niger, Syncephalastrum racemosum, and four untypable isolates. These isolates were further identified by polymerase chain reaction (PCR), and the internal transcribed spacers (ITSs) gene was detected. Four representative isolates were submitted for sequencing and further phylogenetic analysis. The source of duckling infection might be linked to the hatchery environment due to the observed similarity of isolates from both affected birds and the hatchery, as evidenced by phylogenetic analysis. Conclusion: Our findings demonstrated the significance of appropriate hatchery control in preventing infection in young ducklings. Furthermore, the use of molecular identification techniques would be helpful for tracing the source of infection and rapid diagnosis of Aspergillus in the field.J. Adv. Vet. Anim. Res., 10(4): 763–772, December 2023http://doi.org/10.5455/javar.2023.j732